Preparation method of carbon cage-in-cage / carbon coated nickel composite material with infrared stealth performance, obtained product and application
By introducing magnetic carbon into carbon materials to coat nickel nanoparticles and building a cage structure, the structure of carbon materials is optimized, and the problem of impedance mismatch and limited absorption bandwidth of carbon materials in electromagnetic wave absorption and infrared stealth is solved, and the problem of carbon materials is achieved. The high performance and stability of composite materials have a wide range of application prospects.
Patent Information
- Application Number
- CN202411686522.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Existing carbon materials have impedance mismatch, limited absorption bandwidth and structural instability in electromagnetic wave absorption and infrared stealth, which is difficult to meet the needs of modern warfare for broadband and high-performance materials.
By introducing magnetic carbon coated nickel nanoparticles and building a cage structure, the structure of the carbon material is optimized, and the carbon cage/carbon coated nickel composite material is prepared, and the hollowing of the material is controlled by gradient pyrolysis method and hydrochloric acid etching technology. Structure and nickel etching degree.
It has achieved good conductivity, electromagnetic wave absorption performance and low infrared emissivity of composite materials, overcome the shortcomings of pure carbon materials, and has a wide range of application prospects in the fields of infrared stealth and electromagnetic wave absorption.
Smart Images

Figure CN119457110A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon-in-cage / carbon-coated nickel composite material with infrared stealth performance, and also relates to a product obtained according to the method and application of the product in electromagnetic wave absorption and infrared fields, belonging to the technical field of nano material preparation and application. Background Art
[0002] With the rapid development of wireless communication equipment and power transmission technology, electromagnetic radiation and pollution problems are becoming increasingly serious, which may interfere with equipment operation and endanger human health. Microwave absorbing materials are one of the effective means to solve electromagnetic radiation and pollution because they can effectively absorb electromagnetic energy through dielectric loss or magnetic loss. So far, various electromagnetic wave absorbing materials including metal oxides, conductive polymers and ceramics have been widely studied. In practical applications, absorbents must not only have strong absorption and wide bandwidth, but also be light in weight. Among various candidate materials, carbon materials have attracted great attention due to their high conductivity, large specific surface area, light weight and strong chemical stability. However, pure carbon materials have certain limitations. Their high conductivity leads to skin effect, resulting in impedance mismatch, which increases microwave reflection rather than absorption. In addition, the single loss mechanism of pure carbon materials usually limits the absorption bandwidth to below 4 GHz, making it difficult to achieve strong absorption over a wide frequency range.
[0003] Recent advances in electromagnetic wave absorption materials have shown that the addition of magnetic components, including ferromagnetic metals, oxides, and alloys, to carbon materials significantly enhances broadband absorption by improving impedance matching and introducing dielectric and magnetic losses. Hollow structured materials, in particular, show great promise as microwave absorbers, with lower reflection losses (RL) than bulk materials due to their large internal cavities and double-sided surfaces. The large cavity not only reduces the overall weight of the absorber, but also facilitates multiple reflections and scattering of electromagnetic waves, increasing the effective path length and extending the absorption bandwidth. In addition, the double-sided surfaces provide multiple uniform inhomogeneous interfaces, resulting in a strong interfacial polarization effect, which improves dielectric losses and further enhances the overall absorption efficiency. Unfortunately, conventional fabrication methods, such as high-temperature pyrolysis, solvothermal methods, and solid template methods, often lead to undesirable problems, including nanoparticle aggregation and microstructural collapse. Therefore, achieving precise control over the interface properties and optimizing the synergy between dielectric and magnetic properties are essential for the development of lightweight, broadband, and high-performance microwave absorbers.
[0004] With the advancement of infrared and radar detection technology, traditional single-band stealth materials can no longer meet the needs of modern warfare. Therefore, the development of radar / infrared compatible stealth materials has become a top priority. Summary of the invention
[0005] In view of the shortcomings of carbon materials in electromagnetic wave absorption, infrared stealth and other aspects, the present invention provides a method for preparing a carbon-in-cage / carbon-coated nickel composite material with infrared stealth performance and the resulting product. The method has a simple process, and the structure of the carbon material is optimized by introducing magnetic carbon-coated nickel nanoparticles and constructing a cage-in-cage structure. The resulting composite material has a stable structure, good electrical conductivity, electromagnetic wave absorption performance, and low infrared emissivity, and has wide application value in the fields of infrared stealth, electromagnetic wave absorption, etc.
[0006] The specific technical solutions of the present invention are as follows:
[0007] A method for preparing a carbon-in-cage / carbon-coated nickel composite material, the method comprising the following steps:
[0008] (1) preparing nickel microspheres;
[0009] (2) calcining the nickel microspheres and urea under an inert atmosphere to obtain a NC / Ni composite material;
[0010] (3) The NC / Ni composite material is placed in dilute hydrochloric acid for etching to obtain a carbon-in-cage / carbon-encapsulated nickel composite material - NC / Ni (HS, Hollow structure).
[0011] Furthermore, nickel microspheres can be prepared by methods disclosed in the prior art, for example, by hydrothermal reaction. In a specific embodiment of the present invention, a method for preparing nickel microspheres is provided, which specifically includes the following steps: uniformly mixing nickel chloride hexahydrate, methanol and water, then adding hydrazine hydrate under stirring, mixing uniformly and heating to react, collecting the product after the reaction, washing, and obtaining nickel microspheres.
[0012] Furthermore, in the above-mentioned nickel microsphere preparation process, the reactants are nickel chloride hexahydrate and hydrazine hydrate, and the solvents are methanol and deionized water. In the mixture formed by nickel chloride hexahydrate, hydrazine hydrate, methanol and water, the concentration of nickel chloride hexahydrate is 0.023g / mL-0.025g / mL; the concentration of hydrazine hydrate (present in the form of solution, its concentration is 80wt%) is 0.036mL / mL-0.039mL / mL; the concentration of methanol is 0.24mL / mL-0.25mL / m L; the concentration of water is the remaining part except nickel chloride hexahydrate, hydrazine hydrate and methanol. By adjusting the addition amount of hydrazine hydrate, the morphology of nickel microspheres can be controlled. Experiments show that the addition amount of hydrazine hydrate has a great influence on the morphology and performance of the final product, is the key to the formation of the composition and morphology of the final product, and is also the key to the electromagnetic wave absorption performance of the composite material. Preferably, the addition amount of hydrazine hydrate is 0.038mL / mL.
[0013] Furthermore, in the above nickel microsphere preparation process, hydrazine hydrate is preferably added under strong stirring. After hydrazine hydrate is added and mixed evenly, the mixture is heated to 100° C. for reaction, and the reaction time is 2-4 hours.
[0014] Furthermore, in step (2), the mass ratio of nickel microspheres to urea is 1:3-6, for example, 1:3, 1:4, 1:5, 1:6.
[0015] Furthermore, in step (2), the inert atmosphere is provided by an inert gas such as nitrogen or argon, and the inert gas is continuously introduced into the system during the reaction, with the amount of the inert gas introduced being 30-40 mL / min.
[0016] Further, in step (2), the nickel microspheres and urea are roasted, and the urea generates gaseous nitrogen and carbon source, and a carbon layer is formed on the surface of the nickel microspheres. At the same time, the nickel microspheres are decomposed into multiple nanoparticles, and enter the carbon layer through solid diffusion, or enter the interior of the carbon layer and continue to coat the carbon layer on its surface to form carbon-coated nickel balls, forming NC / Ni composite materials. The roasting is carried out in two stages, and the roasting procedure is: firstly heating to 350-450°C, for example, 350°C, 400°C, 450°C, and roasting for 1-1.5h; then heating to 500-650°C, for example, 500°C, 550°C, 600°C, 650°C, and roasting for 1.5-2h. The heating rate during roasting is preferably 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min.
[0017] Further, in step (3), the concentration of dilute hydrochloric acid is 0.9-1.1 mol / L, and the exposed or partially exposed nickel in the NC / Ni composite material is etched by the action of the acid. The temperature of the acid treatment is 85-95°C, for example, 85°C, 90°C, 95°C. The treatment time is generally 3-12h, for example, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h. Experiments show that the reaction time has a certain effect on the morphology of the final product and also has a certain effect on the electromagnetic wave absorption performance of the composite material. Preferably, the reaction time is 10h.
[0018] The present invention uses nickel microspheres as templates and catalysts, firstly realizes the decomposition of nickel spheres and the coating of carbon layers by gradient pyrolysis, and then etches away the exposed or partially exposed nickel cores by hydrochloric acid heat treatment, so as to obtain a NC / Ni(HS) composite material with special morphology and excellent performance. During the gradient pyrolysis, the nickel microspheres and urea are placed in an inert gas environment for roasting. During the roasting process, the nickel microspheres serve as catalysts and templates, catalyzing urea to form a uniform carbon layer on its surface, and during the roasting process, the nickel microspheres are dispersed into multiple nanospheres and catalyzing urea to form a uniform carbon layer on its surface. During the subsequent hydrochloric acid heat treatment, the nickel that is not coated with the carbon layer or partially coated with the carbon layer is etched away to form a composite material of carbon cage / carbon-coated nickel---NC / Ni(HS). In the composite material, a plurality of carbon nano cages are confined in a micro cage, and a plurality of carbon-coated nickel nano particles are embedded on the carbon shell of the carbon cage and in the cage, and the carbon micro cage and the carbon nano cage are both porous structures, and the etching degree of nickel can be accurately controlled by controlling the etching time, so that the composite material forms a special hollow structure. The structure of the cage in the carbon cage of the present invention solves the problem of excessively high conductivity of the carbon material very well, and the nickel nano particles are coated by a dense carbon layer, and the carbon-coated nickel nano particles are uniform in size in the shell layer and cage of the carbon cage, and no agglomeration phenomenon occurs, which solves the problem of agglomeration and easy oxidation of nickel nano particles very well, and greatly improves the electromagnetic wave absorption and infrared stealth performance of the carbon material.
[0019] The NC / Ni(HS) composite material obtained by the present invention has excellent electrical conductivity, electromagnetic wave absorption performance, low infrared emissivity, and a stable structure, and has good application prospects in the fields of electromagnetic wave absorption and infrared stealth, overcoming the shortcomings of pure carbon materials in these fields. Therefore, the NC / Ni(HS) composite material prepared by the present invention is also within the protection scope of the present invention.
[0020] The invention also provides application of the NC / Ni(HS) composite material as a microwave absorbent.
[0021] The present invention also provides application of the NC / Ni(HS) composite material in the field of electromagnetic wave absorption, and the NC / Ni(HS) composite material can be used as an electromagnetic wave absorption material.
[0022] The present invention also provides application of the NC / Ni(HS) composite material in the field of infrared stealth, and the NC / Ni(HS) composite material can be used as an infrared stealth material.
[0023] Compared with the prior art, the advantages of the present invention are:
[0024] (1) The present invention combines hydrothermal reaction, gradient pyrolysis and hydrochloric acid etching to prepare NC / Ni(HS) composite materials, and the preparation process is simple and easy;
[0025] (2) The present invention prepares a NC / Ni(HS) composite material with a cage-in-cage structure, and uses hydrochloric acid thermal etching to control the degree of removal of exposed nickel, which can accurately control the hollowness of the composite material and effectively solve the problem of small specific surface area and high density of nickel microspheres; and the nickel nanoparticles are coated with a dense carbon layer, which effectively solves the problems of agglomeration and easy oxidation of nickel nanoparticles, has many active sites, and excellent performance.
[0026] (3) The NC / Ni(HS) composite material prepared by the present invention is a carbon-encapsulated nickel-modified carbon micro-cage-encapsulated nano-cage structure, which has good conductivity and a stable structure. Experiments have shown that its performance is significantly improved compared with that of pure nickel microspheres. Due to its stable structure and low infrared emissivity, it has broad application prospects in infrared stealth.
[0027] (4) The NC / Ni(HS) composite material prepared by the present invention has strong thermal stability, excellent electrical conductivity and electromagnetic wave absorption performance, and has broad application prospects in electromagnetic wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The scanning electron microscope images of the samples of the present invention are (a) nickel microspheres, (b) NC / Ni, (c) NC / Ni(HS)-3, (d) NC / Ni(HS)-5, (e) NC / Ni(HS)-7, and (f) NC / Ni(HS)-10.
[0029] Figure 2 Transmission electron microscopy images of the samples of the present invention, (a) nickel microspheres, (b) NC / Ni.
[0030] Figure 3 Transmission electron microscope images of the samples of the present invention, (a) NC / Ni(HS)-3, (b) NC / Ni(HS)-5, (c) NC / Ni(HS)-7, (d) NC / Ni(HS)-10, (e) high-resolution image of carbon-coated nickel nanoparticles, and (f) element surface distribution map.
[0031] Figure 4 Electromagnetic parameter diagrams of nickel microspheres and NC / Ni, (a) the real part of the complex dielectric constant, (b) the imaginary part of the complex dielectric constant, (c) the real part of the complex magnetic permeability, and (d) the imaginary part of the complex magnetic permeability.
[0032] Figure 5 Electromagnetic parameter diagram of NC / Ni(HS), (a) real part of complex permittivity, (b) imaginary part of complex permittivity, (c) real part of complex magnetic permeability, (d) imaginary part of complex magnetic permeability.
[0033] Figure 6 Electromagnetic wave absorption performance diagram of nickel microspheres (a) and NC / Ni (b).
[0034] Figure 7 The electromagnetic wave absorption performance diagram of NC / Ni(HS), (a) NC / Ni(HS)-3, (b) NC / Ni(HS)-5, (c) NC / Ni(HS)-7, (d) NC / Ni(HS)-10.
[0035] Figure 8 The infrared emissivity diagram of NC / Ni(HS)-10; (a) infrared emissivity of the sample at 3-5μm at different temperatures; (b) infrared emissivity of the sample at 8-14μm at different temperatures; (c) infrared emissivity comparison diagram; (d) infrared emissivity curve versus wavelength. DETAILED DESCRIPTION
[0036] The present invention is described in detail below through specific examples, but the use and purpose of these exemplary implementation modes are only used to illustrate the present invention, and do not constitute any form of limitation on the actual protection scope of the present invention, nor limit the protection scope of the present invention to them.
[0037] Example 1 Preparation of NC / Ni(HS) composite material
[0038] (1) Synthetic nickel microspheres
[0039] 500 mg of nickel chloride hexahydrate was dissolved in a mixed solution containing 5 mL of methanol and 15 mL of ionized water. After mixing evenly under strong magnetic stirring, 800 μL of hydrazine hydrate (concentration 80 wt%) was added to the mixed solution. After mixing evenly under strong magnetic stirring, the mixed solution was transferred to a hydrothermal autoclave and reacted at 100° C. for 3 h. After cooling to room temperature, the black powder was collected with a magnet, rinsed three times with ultrapure water and ethanol respectively, and dried under vacuum at 70° C. to obtain nickel microspheres.
[0040] (2) Preparation of NC / Ni by gradient pyrolysis
[0041] 100 mg of nickel microspheres and 500 mg of urea were spread flat in a porcelain boat and transferred into a tubular furnace. Urea was located at the air inlet end of the tubular furnace. Argon was introduced into the tubular furnace at a rate of 40 mL / min. A two-stage calcination method was used. First, the temperature was raised to 400 ° C at a rate of 2 ° C / min and calcined for 1 h. Subsequently, the temperature was continued to rise to 550 ° C at a rate of 2 ° C / min and calcined for 2 h. The resulting product was a NC / Ni composite material.
[0042] (3) Preparation of NC / Ni(HS) composites by hydrochloric acid thermal etching
[0043] The obtained NC / Ni composite material was immersed in 1M HCl and reacted in an oil bath at 90°C for 3h, 5h, 7h, and 10h to obtain a NC / Ni(HS) composite material. According to the reaction time, the products were named NC / Ni(HS)-3, NC / Ni(HS)-5, NC / Ni(HS)-7, and NC / Ni(HS)-10.
[0044] Nickel microspheres play several key roles in the preparation of NC / Ni(HS): (1) as a catalyst to catalyze the growth of a highly graphitized nitrogen-doped carbon (NC) layer on the nickel surface; (2) as a template to help form a hollow structure by etching the nickel core; and (3) as a nickel source to incorporate nickel nanoparticles into the nitrogen-doped carbon shell through a solid diffusion process. Composite materials consisting of a nitrogen-doped carbon shell and a nickel core were prepared by urea pyrolysis. Finally, NC / Ni(HS) composites with a well-structured hollow core were obtained by selectively etching the exposed or partially exposed nickel core inside. Scanning electron microscopy and transmission electron microscopy images showed that the original nickel exhibited a distinct microsphere morphology, characterized by a solid structure and many nanosheets ( Figure 1 a and Figure 2 a). The metallic nature and large surface area of nickel favor the decomposition of urea to generate gaseous nitrogen and carbon source, which are then converted into nitrogen-doped graphitized carbon layers. The NC / Ni intermediate retains the same morphological features as the original nickel ( Figure 1 b). The thickness of the carbon shell uniformly wrapped on the particle surface is about 20nm ( Figure 2 b). During the acid etching process, the etched edges gradually become highly visible as the etching time increases. As expected, there is no significant change in the size of the microcages of the samples before and after acid etching. After the acid removes the metallic nickel core, NC / Ni transforms into NC / Ni(HS)( Figure 1 c- Figure 1 f). The NC / Ni(HS) sample has a cage-like structure, which is composed of many small nanocage carbon chambers as subunits ( Figure 3 a- Figure 3 d). Highly ordered stripes of graphitic carbon were observed in high-resolution transmission ( Figure 3 e1), indicating high crystallinity. In addition, no obvious aggregation of nickel nanoparticles can be seen on the carbon layer, indicating good dispersion of nickel species doped in the carbon lattice. Figure 3 e2 shows a lattice spacing of 0.20 nm, corresponding to the (111) plane of nickel. High-angle annular dark field scanning transmission electron microscopy (HAADF) and elemental surface distribution images ( Figure 3 f) further confirms this observation, showing that C, Ni, and N elements are uniformly distributed throughout the NC / Ni(HS) matrix.
[0045] Application Example 1
[0046] Application of NC / Ni(HS) composite materials in electromagnetic wave absorption:
[0047] (1) Add sample and paraffin in a beaker at a mass ratio of 5:95.
[0048] (2) Place the beaker on a 60°C hot plate to mix the sample and paraffin evenly.
[0049] (3) The uniformly mixed sample and paraffin are placed in a mold to prepare a ring with an inner diameter of 3.04 mm, an outer diameter of 7.00 mm, and a thickness of 2.00 mm.
[0050] (4) Place each ring on a vector grid analyzer to measure its electromagnetic parameters.
[0051] The real part (ε′) and imaginary part (ε″) of the complex dielectric constant represent the ability to store and dissipate electrical energy, respectively. The real part (μ′) and imaginary part (μ″) of the complex magnetic permeability represent the magnetic energy storage and dissipation capabilities, respectively. Figure 4 As shown in Figure 2, the ε′ values of Ni and NC / Ni are 3.0 and 2.6, respectively, which are almost constant, while the ε″ value is close to 0, indicating that Ni and NC / Ni have limited ability to absorb electromagnetic energy. According to previous reports, the introduction of hollow structures is an effective strategy to improve impedance matching and dielectric loss capabilities. As expected, the ε′ and ε″ values increase rapidly with the extension of the acid etching time ( Figure 5 a, 5b). In the frequency range of 2.00~18.00GHz, the ε′ values of NC / Ni(HS)-3, NC / Ni(HS)-5, NC / Ni(HS)-7 and NC / Ni(HS)-10 vary between 7.3~5.9, 9.0~6.7, 9.5~5.9 and 11.3~5.8, respectively. Meanwhile, the ε″ values of NC / Ni(HS)-3, NC / Ni(HS)-5, NC / Ni(HS)-7 and NC / Ni(HS)-10 vary between 1.0~1.2, 2.4~1.8, 2.9~1.5 and 3.6~2.4, respectively. According to the free electron theory (ε″≈φ / 2πε0f, where φ and ε0 represent conductivity and free space impedance, respectively), ε″ is positively correlated with φ, and a large φ is conducive to the migration and jumping of electrons, thereby increasing the conduction loss. Figure 4 c, 4d and 5c, 5d show the complex magnetic permeability curves of the obtained samples. With the increase of etching time, μ′ gradually increases, which may be due to the uniform distribution of Ni in the carbon layer. In addition, several natural resonance peaks are found in the μ″ curve, which may be caused by loss and magnetic coupling effects.
[0052]
[0053] RL=20lg|(Z in -Z0) / (Zin +Z0)| (Equation 2)
[0054] Where Z in is the input impedance of the absorber, Z0 is the free space impedance, μ r is the relative complex permeability (μ r =μ′-iμ″), ε r is the complex dielectric constant (ε r =ε′-iε″), d is the thickness of the absorber, c and f are the speed and frequency of light respectively.
[0055] The electromagnetic wave absorption performance of materials is usually evaluated using the reflection loss (RL) value (Equations 1 and 2). RL values less than -10 dB are considered to be effective absorption, indicating that more than 90% of the incident electromagnetic waves are absorbed. In order to highlight the advantages of the Ni site-anchored NC / Ni(HS) hollow porous structure, the three-dimensional RL graphs of the prepared samples were systematically compared. When the filling ratio was 4 wt.%, pure Ni microspheres did not show electromagnetic wave absorption performance (no RL ≤ -10 dB) ( Figure 6 a), even with nitrogen-doped carbon shell, the electromagnetic wave absorption performance is not improved ( Figure 6 b). Interestingly, the electromagnetic wave absorption performance of the samples significantly improved with the etching of the Ni core. Specifically, the RL of NC / Ni(HS)-3 at 3.00 mm thickness was -11.26 dB, and the effective bandwidth (EAB) at 3.10 mm thickness was calculated to be 1.52 GHz ( Figure 7 a). It is worth noting that with the increase of etching time, the electromagnetic wave absorption performance is significantly enhanced, while the matching thickness is also reduced. When the thickness is 5.00mm, 3.20mm and 2.63nm, the minimum RL (RL min ) values are -19.37dB (5.44GHz), -24.25dB (8.64GHz) and -63.67dB (10.16GHz) respectively. Figure 7 b-7d), it is calculated that when the thickness is 2.00mm, the maximum EAB (EAB max ) values are 3.92 GHz, 4.8 GHz and 6.16 GHz, respectively. Compared with NC / Ni(HS)-3, NC / Ni(HS)-10 not only has a reduced matching thickness (from 3.0 to 2.63 mm), but also has an enhanced absorption intensity (from -11.26 to -63.67 dB) and a wider EAB (from 1.52 to 6.16 GHz). The RL of the prepared NC / Ni(HS) samples was systematically compared. min and EAB maxThe absorption peak of NC / Ni(HS)-10 can be tuned from C-band (4-8 GHz) to Ku-band (12-18 GHz) by adjusting the etching time.
[0056] Application Example 2
[0057] Application of NC / Ni(HS) composite materials in infrared stealth field:
[0058] The samples were pressed into circular sheets and the infrared emissivity was tested in the atmospheric window frequency band using an infrared spectrometer.
[0059] Low infrared emissivity is an important condition for achieving infrared stealth. In order to prove the infrared stealth performance of NC / Ni(HS)-10, the infrared emissivity of NC / Ni(HS)-10 was tested in the range of 25-400°C. Without changing the surface temperature of the material, the infrared radiation characteristics can be reduced by adjusting the node emissivity. In the atmospheric environment, infrared radiation of different wavelengths will be attenuated to varying degrees. The main working bands of infrared detectors are in the relatively transparent 3-5μm and 8-14μm atmospheric window areas. Due to its excellent electromagnetic wave performance, NC / Ni(HS)-10 was selected for detailed analysis. Figure 8 a and 8b show the changes of infrared emissivity of NC / Ni(HS)-10 in the 3-5μm and 8-14μm bands with temperature. From room temperature to 400℃, the infrared emissivity of NC / Ni(HS)-10 increases slightly, and the average emissivity is only 0.76 (3-5μm) and 0.79 (8-14μm) ( Figure 8 c). Figure 8 d shows a more detailed curve of infrared emissivity versus wavelength. The larger specific surface area of NC / Ni(HS)-10 is conducive to the internal refraction and absorption of infrared light, which attenuates the infrared radiation energy emitted by the target and reduces the infrared emissivity. The special hollow channel structure enhances the thermal insulation performance and reduces the infrared radiation energy density of the sample. The surface of the NC / Ni(HS)-10 sample is smooth and the particle size is uniform. The surface roughness is positively correlated with the particle size uniformity and emissivity, which is conducive to reducing the emissivity. The air space between the shells in the hollow structure acts as a thermal insulation layer, further reducing the infrared radiation energy density.
Claims
1. A method for preparing a carbon cage-in-cage / carbon-coated nickel composite material, characterized in that The following steps are involved: (1) preparing nickel microspheres; (2) calcining the nickel microspheres and urea under an inert atmosphere to obtain a NC / Ni composite material; (3) The NC / Ni composite material is placed in dilute hydrochloric acid for etching to obtain a carbon-in-cage / carbon-coated nickel composite material.
2. The preparation method according to claim 1, characterized in that: The preparation method of nickel microspheres is as follows: nickel chloride hexahydrate, methanol and water are mixed evenly, hydrazine hydrate is added under stirring, the mixture is mixed evenly and then the temperature is raised to react, and the product is collected and washed after the reaction to obtain nickel microspheres.
3. The preparation method according to claim 2, characterized in that: When preparing nickel microspheres, at least one of the following conditions is included: Condition 1: In a mixture formed by nickel chloride hexahydrate, hydrazine hydrate, methanol and water, the concentration of nickel chloride hexahydrate is 0.023 g / mL-0.025 g / mL; Condition 2: In a mixture of nickel chloride hexahydrate, hydrazine hydrate, methanol and water, the concentration of hydrazine hydrate is 0.036 mL / mL-0.039 mL / mL; Condition 3: In a mixture of nickel chloride hexahydrate, hydrazine hydrate, methanol and water, the concentration of methanol is 0.24 mL / mL-0.25 mL / mL; Condition 4: reaction temperature is 100°C; Condition 5: Reaction time is 2-4h.
4. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of nickel microspheres to urea is 1:3-6.
5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the nickel microspheres and urea are first heated to 350-450° C. in an inert atmosphere and calcined for 1-1.5 h, and then heated to 500-650° C. and calcined for 1.5-2 h.
6. The preparation method according to claim 1, characterized in that: In step (3), the concentration of dilute hydrochloric acid is 0.9-1.1 mol / L; preferably, the etching temperature is 85-95° C., and the etching time is 3-12 h.
7. A product obtained by the method for preparing a carbon-in-cage / carbon-coated nickel composite material according to any one of claims 1 to 6.
8. Use of the carbon-in-cage / carbon-coated nickel composite material as claimed in claim 7 as a microwave absorber.
9. Application of the carbon-in-cage / carbon-coated nickel composite material according to claim 7 in the field of electromagnetic wave absorption.
10. Application of the carbon-in-cage / carbon-coated nickel composite material according to claim 7 in the field of infrared stealth.
Citation Information
Patent Citations
Preparation method of nitrogen-doped three-dimensional porous carbon loaded with nano cobalt and application thereof in lithium sulfur batteries
CN110336032A
Method for preparing three-dimensional hierarchical porous carbon material and regulating and controlling pore diameter thereof
CN110713176A
Preparation method of black phosphorene self-supporting negative electrode material with porous structure
CN114725362A
Preparation method and application of microporous conversion alloying material
CN114864892A
Carbon-coated nickel nano carbon cage composite material and preparation method thereof, lithium-sulfur battery positive active material and preparation method and application thereof
CN115832297A